In situ synthesis of water dispersible bovine serum albumin capped gold and silver nanoparticles and their cytocompatibility studies - Murawala, Priyanka; Phadnis, S. M.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
A simple and convenient one step room temperature method is described for the synthesis of bovine serum albumin (BSA) capped gold and silver nanoparticles. BSA reduces silver ions to silver nanoparticles but does not directly reduce gold ions to gold nanoparticles at room temperature and varying pH conditions. However, when silver and gold ions are simultaneously added to BSA, silver ions get reduced to metallic silver first and these in turn reduce gold ions to gold nanoparticles through a galvanic exchange reaction. The so synthesized silver and gold nanoparticles are easily water dispersible and can withstand addition of salt even at high concentrations. It is shown that the capped protein retains its secondary structure and the helicity to a large extent on the nanoparticles surface and that the protein capping makes the nanoparticles cytocompatible. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag and Au nanoparticles; Bovine serum albumin; Cytocompatibility; Galvanic exchange reaction; Reductive synthesis